The Project of Arquitetura Nova: Practice and Form - Davide Sacconi (Textos de Tecnología, 2022)
Rethinking the role of the architect and design across scales and scopes is an urgent imperative in the face of the tremendous social, political and environmental challenges of the next decades. Yet, the endeavour of dismantling and rebuilding the means and the ends of what is essentially a very conservative form of production is daunting. A crucial step in pursuing this ambition is the search for exemplary practices that dare to challenge the dominant forces and lines of development and, therefore, are usually erased from the prevailing narratives. At the core of this research is the idea that building is both a mode of production— a process that requires a specific organisation of labour—and at the same time its outcome—a material form that defines a specific use and organisation of life through presence. Hence, building, as both process and form, contributes decisively to the production of subjectivity. However, while building can be understood as the mere implementation of existing forms of production, architecture is instead the materialisation of a project that aims at constructing subjects’ other or more precisely at bridging the gap between existing and imagined subjects, between dominant and alternative forms of production and life. From this premise, three fundamental questions emerge: how should the process that materialises the project unfold; who should be the subject that imagines new forms of production and life; and what form should architecture take. The work of the Brazilian collective Arquitetura Nova offers coherent answers to these questions, grounded in a radical critique of the specific historical conditions, and elaborated through the experimentation with a different form of architectural practice.